A new model for the identification of subcritical surface subsidence in deep pillarless mining. (November 2021) - Pan, Ruikai; Li, Yong; Wang, Hui; Chen, Jie; Xu, Youlin; Yang, Hongyun; Cao, Shugang
Highlights: L-shaped PKS failure caused super-subcritical to subcritical subsidence transition. Developed L-shaped plate model to identify subsidence state. A three-year field measurement for surface subsidence was performed. L-shaped plate model agrees well with the FEM and field measurements. Abstract: The identification of the subsidence stage is vital for the surface infrastructure protection above underground mining panels, while prior studies have only focused on shallow mining with large interpanel pillars. In this study, we aimed to develop a new model to identify the initiation of subcritical subsidence in deep pillarless mining. The key stratum theory was used to transform the problem of stage identification for surface subsidence into the primary key stratum (PKS) failure. The findings show that the PKS in deep mining can remain stable after a single panel is extracted. The narrow pillar gradually loses its structural integrity and fails to isolate the movement of PKS above two panels as the second panel passes it. Consequently, the PKS above two panels integrally fails as an L-shaped plate, causing the transition from super-subcritical to subcritical subsidence stage. According to these findings, the L-shaped PKS model was developed using the theory of elastic plates to determine the critical span of PKS failure and identify the occurrence of subcritical subsidence in pillarless mining. The model was validated using a three-year field measurement data on surface subsidence in Longtan coal mine. This study contributes to the understanding of subsidence mechanism in deep pillarless mining and provides new insight into designing pillarless mining with surface subsidence control.